Farmers' satisfaction with compensations for farmland expropriation in China: Evidence from micro-level data. Issue 4 (5th November 2018) - Qu, Song; Heerink, Nico; Xia, Ying; Guo, Junping
Abstract : Purpose: The purpose of this paper is to examine the impact of the compensation amount as well as the mode through which compensations are paid on farmers' satisfaction with the compensation received for farmland expropriation in China. Design/methodology/approach: Using rural household survey data collected among 450 households in three provinces, located in eastern, central and western China, this paper estimates the impacts of compensation payments, compensation modes, household characteristics and other control variables on farmers' satisfaction applying an ordinal probit model. Findings: The major findings are: farmers' satisfaction with the compensation depends not only on the size of the compensation but also on the gap between the compensation and the market value of the expropriated land; and the compensation amount positively affects farmers' satisfaction when the social security compensation mode is used, but does not significantly affect farmers' satisfaction when other modes are used. Originality/value: First, it contributes to the literature on farmland expropriation by providing empirical evidence of the direct impact of the compensation amount and other factors on the degree of farmers' satisfaction with farmland compensations. Second, potential interactions between compensation amount and compensation mode are taken into account in estimating factors affecting farmers' satisfaction.